PENGEMBANGAN MODUL PENGENDALIAN PEMBELAHAN SEL UNTUK MENUMBUH KEMBANGKAN KETERAMPILAN BERPIKIR KRITIS - murtini, iin (Pendidikan Biologi Universitas PGRI Ronggolawe Tuban, 2021)
Modules are teaching materials that are indispensable in learning to assist teachers in delivering learning materials in order to improve student competence, one of which is critical thinking skills. This study aims to produce products in the form of cell division control modules to develop critical thinking skills. The method used in this research is ADDIE (Analyze, design, develop, implement, and evaluate). Modules are validated by media experts, materials experts, field practitioners, and readability and practicality trials. The results of validation by material expert validators, media expert validators and field practitioners, were obtained respectively 91.02%, 91.41%, and 90.21% with very valid criteria and can be used without the need for revision. The results of the practicality test are 91.25% with very practical criteria and can be used without the need for revision.